Efficacy and safety of short-acting β-blockers in patients with sepsis-associated cardiac dysfunction: a systematic review and meta-analysis of randomized controlled trials - Zheng, Min'an; Wang, Jin; Xie, Pingchang; Guo, Shijun; Chen, Benjian; He, Zhuogen; Yao, Guoyan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe role of ultra-rapid β-blockers in sepsis-associated cardiac dysfunction remains controversial, with conflicting evidence regarding mortality benefits and safety concerns in hemodynamically unstable patients.MethodsThis study retrieved relevant reports on randomized controlled trials of ultra-rapid β-blockers conducted for adult patients with sepsis-associated cardiac dysfunction, up to and including the date of May 30, 2025, from the databases of PubMed, Web of Science, Cochrane Library and Embase. Primary outcomes were 28-day mortality and adverse events; secondary outcomes included heart rate control and mean arterial pressure (MAP) at 48 h. Random-effects models calculated risk ratios (RR) or standardized mean differences (SMD) with 95% confidence intervals (CI). Heterogeneity was assessed using I² statistics.ResultsEight studies reported 28-day mortality, showing no significant reduction with ultra-rapid β-blockers (RR, 0.84, 95% CI: 0.67–1.06; P = 0.15; I² = 54%). Safety data from four studies indicated no increased adverse events (RR, 1.04, 95% CI: 0.82–1.33; P = 0.72; I² = 0%). Paradoxically, ultra-rapid β-blockers were associated with worse heart rate control (RR, 1.51, 95% CI: 1.00–2.29; P = 0.05). MAP at 48 h showed no intergroup difference (SMD, −0.85, 95% CI: −2.24–0.54).Conclusionultra-rapid β-blockers demonstrate an acceptable safety profile without compromising hemodynamic stability but fail to reduce 28-day mortality in sepsis-associated cardiac dysfunction patients. The inferior heart rate control suggests potential physiological incompatibility in this population. Precision targeting based on adrenergic activity and cardiac phenotyping warrants investigation.